Capital adequacy and corporate performance of non-financial firms: Empirical evidence from Nigeria - Olubunmi Adewole Ogunode; Olaolu Ayodeji Awoniyi; Ayodeji Temitope Ajibade (Cogent Business & Management, 2022)
This research assesses the effect of capital adequacy on the corporate performance of quoted non-financial firms operating in Nigeria. Several studies on the influence of capital adequacy on corporate performance have been conducted without specific focus on non-financial entities despite their growing contribution to the country's gross domestic product (GDP). The study utilized the ex-post facto research design using secondary data obtained for the period 2011-2020. A sample of thirty-eight (38) out of sixty-three (63) listed non-financial firms were purposively selected while data obtained were analyzed using multivariate regression. The study found that while capital adequacy ratio, equity capital/total assets ratio and cost income ratio negatively affected corporate performance, debt equity ratio and firm size positively influenced corporate performance of quoted non-financial firms operating in Nigeria. It therefore concluded that firm size and profitable use of debt capital in the capital mix of non-financial firms are key factors that can positively drive their corporate performance. Consequently, it recommended that the management of non-financial firms should explore opportunities inherent in profitable use of debt capital to further improve their performance and hence returns to their respective stakeholders. Additionally, regulators of non-financial firms operating in Nigeria should strengthen the risk management monitoring framework to ensure market discipline and balanced growth and development of the firms.
Keywords: 650; capital adequacy; CAR ratio; corporate performance; non-financial firms; regression analysis